2012
DOI: 10.1155/2012/878052
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide as an Endogenous Modulator in Mitochondria and Mitochondria Dysfunction

Abstract: Hydrogen sulfide (H2S) has historically been considered to be a toxic gas, an environmental and occupational hazard. However, with the discovery of its presence and enzymatic production through precursors of L-cysteine and homocysteine in mammalian tissues, H2S has recently received much interest as a physiological signaling molecule. H2S is a gaseous messenger molecule that has been implicated in various physiological and pathological processes in mammals, including vascular relaxation, angiogenesis, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 62 publications
3
57
0
3
Order By: Relevance
“…Lee and collaborators [28] suggested that the apoptotic effects of NO excess on mice embryos could be related to S-nitrosylation, in exclusion to other any mechanisms. The latter effects were closely associated with lipid-rich organelles (mitochondria and endoplasmic reticulum) [28,86]. On the other hand, trophoblasts might also be protected from apoptosis via S-nitrosylation of caspase 3 [87].…”
Section: S-nitrosylation Plays Pivotal Role In Modulating Trophoblastmentioning
confidence: 99%
“…Lee and collaborators [28] suggested that the apoptotic effects of NO excess on mice embryos could be related to S-nitrosylation, in exclusion to other any mechanisms. The latter effects were closely associated with lipid-rich organelles (mitochondria and endoplasmic reticulum) [28,86]. On the other hand, trophoblasts might also be protected from apoptosis via S-nitrosylation of caspase 3 [87].…”
Section: S-nitrosylation Plays Pivotal Role In Modulating Trophoblastmentioning
confidence: 99%
“…Так, у мозку ссавців, зокрема в гіпокампі, мозочку та півкулях го-ловного мозку за продукцію H 2 S відповідає фермент цистатіонін-β-синтаза (CBS), тоді як в аорті, клубовій кишці, ворітній вені, печінці, нирках та матці його утворення від-бувається переважно цистатіонін-γ-ліазою (CSE) [1]. На мишах з нокаутованим геном ферменту CBS, було відкрито інший шлях синтезу газотрансмітера, а саме за допомо-гою 3-меркаптопіруватсульфуртрансферази (3-MST), яка працює в парі з цистеїнамі-нотрансферазою (CAT) і має цитоплазма-тичну та мітохондріальну локалізацію [1]. Ген ферменту 3-MST експресується також у клітинах ендотелію та гладеньких м'язів судин [2].…”
Section: вступunclassified
“…Hydrogen sulfide is endogenously produced by some enzymes in the mammalian tissues [51] and acts as neuromodulator/ transmitter, and neuro-protector in the brain [51][52][53][54]. It plays an important role in protecting neurons from oxidative stress by scavenging free radicals and reactive species, recovering glutathione levels, inhibiting intracellular Ca 2+ status [51,55].…”
Section: Proposed Mechanisms Of Sulfur-induced Pemmentioning
confidence: 99%
“…It plays an important role in protecting neurons from oxidative stress by scavenging free radicals and reactive species, recovering glutathione levels, inhibiting intracellular Ca 2+ status [51,55]. Hydrogen sulfide is also reported to reduce the generation of reactive oxygen species (ROS) from mitochondria by inhibiting cytochrome c oxidase and suppressing respiration [51]. Furthermore, H 2 S may protect neurons from cellular energy depletion during the stress conditions by serving as substrate to sustain ATP production [51,56].…”
Section: Proposed Mechanisms Of Sulfur-induced Pemmentioning
confidence: 99%
See 1 more Smart Citation